ISLAM PERSPEKTIF DAN PERSPEKTIF ISLAM TENTANG PENDETA SYAIFUDIN IBRAHIM (Analisis Pandangan, Asumsi, dan Tantangan Pendeta Syaifuddin Ibrahim Terhadap Umat Muslim) - nopriyansa, eko (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2020)
The phenomenon of religious people and freedom to choose religion as a belief in life becomes freedom that cannot be bargained. The series of past history reminds religious people that the Presence of Religion is on the most principle principle, in order to be a solution in various aspects of human life, apart from the dark history of Religion which is ridden by the interests of power and vice versa on the power of Religion. Furthermore, the context of the past is a compass of the future of Religion which is burdened by every follower of Religion. The presence of Christianity as a Missionary religion and Islam as a Da'wah religion opened a space for religious social dialogue, because both were involved in Agamanization. Furthermore, the two characteristics possessed by each religion will certainly ignite the enthusiasm of Christian evangelists and preachers on the part of Islam to compete in assuming the truth of the perspective. The presence of this article will open a space for scientific dialogue to the two communities, in exposing the views and assumptions of Reverend Murtadin Saifudin Ibrahim who has an Islamic background and assumes that he is one of the Islamic leaders who then turned to become a Christian priest. Furthermore this article is not an Interference to Saifudin Ibrahim's new beliefs, but this article is to answer Saifudin Ibrahim's assumptions and views on Islam as the largest religion among religious people in Indonesia. In the end, hopefully this article can answer various obscure views and thoughts, and thoughts that intercept the faith in Islam in Indonesia.